PERBANDINGAN ALGORITMA NAZIEF & ADRIANI DENGAN ALGORITMA IDRIS UNTUK PENCARIAN KATA DASAR - Adhi Prasidhatama; Kristien Margi Suryaningrum (Universitas Merdeka Malang, 2018)
Stemming is a process used to search root words. Stemming can be implemented as preprocessing in text processing. There are many stemming algorithms, one of them is Nazief Adriani and Idris. Nazief Adriani algorithm is an algorithm created by Bobby Nazief and Mirna Adriani to find the root word of Bahasa Indonesia. While the Idris algorithm is an algorithm created by Norisma Idris to find the root words of Malay language. Indonesian and Malay have similar language styles, so researchers want to find out whether the Idris algorithm can be used as one of the Indonesian stemming algorithms. To know which algorithm is better, then in this research will be explained about process speed and accuracy of result of each of those algorithm. After knowing the result of comparison of stemming algorithm, hopefully can help you in choosing which algorithm will be used for find root word of Bahasa Indonesia.DOI: https://doi.org/10.26905/jtmi.v4i1.1773